NEMO Gene Mutations in Two Chinese Females with Incontinentia Pigmenti - Jiang J; Zeng J; He Q; Yang J; Wang S; Zhang Z (Dove Medical Press, 2022)
Jingjing Jiang,1 Junjie Zeng,2 Qi He,1 Jiao Yang,1 Shenglan Wang,1 Zhengzhong Zhang1 1Department of Dermatology, Affiliated Hospital of North Sichuan Medical College, Nanchong, Sichuan Province, People's Republic of China; 2Department of Dermatology, Taikang Sichuan Southwest Hospital Company Limited, Chengdu, Sichuan Province, People's Republic of ChinaCorrespondence: Zhengzhong Zhang, Department of Dermatology, Affiliated Hospital of North Sichuan Medical College, 1 Maoyuan South Road, Shunqing District, Nanchong, Sichuan Province, 637000, People's Republic of China, Tel +8618080339898, Email laowaiaeo@163.comPurpose: To identify the mutations of the NEMO gene in two Chinese females with incontinentia pigmenti.Patients and Methods: Patients were both from Nanchong, Sichuan Province. Genomic DNA was extracted from the peripheral blood of patients and patient 1ʹs father. The mutations of the NEMO gene in patient 1 by GAP polymerase chain reaction and Sanger sequencing and her father were detected. NEMO-specific polymerase chain reaction and Sanger sequencing were used to identify the NEMO gene mutation in patient 2.Results: DNA analysis identified a rare frameshift mutation, c.723_c.724insCAGG(p.A242QfsX15) in exon 5 of the NEMO gene in patient 1 with a family history but not in her healthy father. The common deletion of exons 4- 10 of the NEMO gene was found in sporadic patient 2.Conclusion: Our data revealed that the rare frameshift mutation, c.723_c.724insCAGG(p.A242QfsX15) in exon 5 of the NEMO gene in patient 1 and the deletion of exons 4- 10 of the NEMO gene in patient 2 could cause the occurrence of IP. Genetic testing is helpful for early diagnosis and genetic counseling for families.Keywords: Chinese, incontinentia pigmenti, mutation, NEMO gene, NF-κB pathway